FMEA, CFD and FEA TO OPTIMIZE THE DEVELOPMENT OF PRODUCTS WITH 3D PROTOTYPING IN AUTOMOTIVE MECHANICAL PART AFTERMARKET - Part A: FMEA: FMEA, CFD and FEA TO OPTIMIZE THE DEVELOPMENT OF PRODUCTS WITH 3D PROTOTYPING IN AUTOMOTIVE MECHANICAL PART AFTERMARKET - Part A: FMEA - Cavaignac, André Luís de Oliveira; Silva, Luan Henrique Varão; Sousa Júnior, Rúben; Silva, Edilson Morais Lima e; Lima, Ricardo Jorge Cruz (Brazilian Journal of Production Engineering, 2020)
The additive manufacturing area emerges as a powerful tool for use in product development projects - PDP, and in small scale and high specificity manufacturing processes. However, factors such as long printing time, the need to rework prototype layouts and the need for new prints show that the PDP process with 3D prototyping still has points to be improved. In this work it was proposed to use failure modes and effects analysis (FMEA) integrated with occupational safety FMEA (OS-FMEA), together with the application of computational fluid dynamics (CFD) and finite elements analysis (FEA), to optimize the process development of an automotive mechanical part for the aftermarket market, manufactured using 3d printing. To this end, the present work used as a test piece an adapter flange to replace carburetors in collection automobiles. From the application of initial PDP tools an initial product concept was conceived and the first model was developed in a CAD (computer-aided design) environment. This initial model served for the application of FMEA / OS-FMEA for the identification and correction of possible flaws in the model. After the improvements applied and the reduction of all risk priority numbers (RPN) obtained, printing was carried out on additive manufacturing of the defined model. Using the FMEA+CFD+FEA methodology, it was possible to obtain a viable part in just one print, showing the efficiency of the method in optimizing prototyping.
Keywords: 3d prototyping; FMEA; FEA; CFD